A scale for measuring externality-internality - Bagdonas, A.; Pociūtė, L. (Psichologija, 1988)
The paper studies the validity and reliability of a new scale for measuring internality-externality. The standard norms for the number of students and senior pupils are suggested. On the basis of the data obtained during the test of 1, 181 subjects seven grades of internality externality have been established: (1) extremely external personality, (2) highly external personality, (3) external personality, (4) external-internal personality, (5) internal personality, (6) highly internal personality, (7) extremely internal personality. The test was repeated a month later after the first testing (n= 100). The scale proved to be reliable for measuring internality-externality (r=0.75, p
Keywords: Externality-Internality scale; locus of control